Cover Picture. Issue 2 (23rd June 2020) - Unknown
Abstract : Abstract : Cover Picture In article number EOM212021, Yinlong Zhu and co‐workers firstly discover the lattice‐oxygen sites in Ruddlesden‐Popper (RP) crystal structure can be activated for ultrafast oxygen evolution. The proof‐of‐concept RP Sr3(Co0.8Fe0.1Nb0.1)2O7‐δ (RP‐SCFN) oxide exhibits outstanding OER activity due to the activated lattice oxygen sites triggered by high covalency of metal‐oxygen bonds, outperforming the benchmark noble‐metal RuO2 and state‐of‐the‐art oxide‐based catalysts ever reported.